Critique is rooted in skepticism. Review of: Abraham Anderson, The Skeptical Roots of Critique: Hume’s Attack on Theology and the Origin of Kant’s Antinomy, Oxford, Oxford University Press, 2025, 184 pp. - Laursen , John Christian (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Review of Abraham Anderson, The Skeptical Roots of Critique: Hume’s Attack on Theology and the Origin of Kant’s Antinomy, Oxford, Oxford University Press, 2025, 184 pp.